Cancer-Associated PIK3CA Mutations in Overgrowth Disorders. Issue 10 (October 2018) - Madsen, Ralitsa R.; Vanhaesebroeck, Bart; Semple, Robert K.
Abstract : PIK3CA is one of the most commonly mutated genes in solid cancers. PIK3CA mutations are also found in benign overgrowth syndromes, collectively known as PIK3CA -related overgrowth spectrum (PROS). As in cancer, PIK3CA mutations in PROS arise postzygotically, but unlike in cancer, these mutations arise during embryonic development, with their timing and location critically influencing the resulting disease phenotype. Recent evidence indicates that phosphoinositide 3-kinase (PI3K) pathway inhibitors undergoing trials in cancer can provide a therapy for PROS. Conversely, PROS highlights gaps in our understanding of PI3K's role during embryogenesis and in cancer development. Here, we summarize current knowledge of PROS, evaluate challenges and strategies for disease modeling, and consider the implications of PROS as a paradigm for understanding activating PIK3CA mutations in human development and cancer. Highlights: Cancer-associated activating PIK3CA mutations, when occurring in isolation during early development, cause a spectrum of rare disorders characterized by asymmetric, and often severe, excessive tissue growth and malformations. Tissues are not uniformly affected, and, surprisingly, no excess of PIK3CA -associated adult cancers has been described. Evidence that low-dose, repurposed cancer therapies may offer effective precision therapy is beginning to emerge. Mouse models driven by endogenous expression of pathogenic, mosaic PIK3CA alleles only partly recapitulate the disease phenotype. Although it is critical for normal cell growth and survival, the role of PIK3CA in early human development is poorly characterized.